Problematika Pengaturan Sanksi dan Besaran Dana Corporate Social Responsibility di Indonesia - Dwi Adhi Setiawan; Muh Jufri Ahmad (Media Hukum Indonesia (MHI), 2026)
Corporate Social Responsibility (CSR) is a legal obligation for companies that operate in natural resources, as regulated in Article 74 of Law No. 40 of 2007 concerning Limited Liability Companies. However, CSR regulations still face various normative issues, especially related to the absence of provisions that clearly set the required funding amount and the lack of clarity on sanctions for companies that fail to carry out these obligations. This study aims to analyze the urgency of regulating sanctions and funding provisions in CSR implementation as an effort to strengthen the success of its implementation in Indonesia. The research method used is normative legal research with a statutory approach and a conceptual approach. The research results show that the use of the phrase “appropriateness and fairness” in CSR regulations creates normative ambiguity, which leads to legal uncertainty and differences in CSR implementation among companies. In addition, the unclear form and mechanism of sanctions cause CSR obligations to lose their enforceability, potentially making CSR an ineffective legal norm. Based on the theory of certainty, Adam Smith’s theory of justice, and Hans Kelsen’s theory of sanctions, legal reform is needed through the establishment of a measurable minimal standard for CSR funds and clear, firm sanction regulations